Chiral Alkynyl‐Stabilized Ag/Cu Nanoclusters from Spontaneous Resolution. Issue 3 (24th January 2023) - Sun, Xueli; Guo, Zipeng; Tang, Xiongkai; Xu, Zhen; Sun, Jing; Xie, Zhenlang; Nan, Zi‐Ang; Guo, Shuo; Shen, Hui
Abstract: Intrinsically chiral metal nanoclusters with crystal structure are highly desirable to gain deep insights into chirality origin of chiral nanostructures and understand structure‐and‐property relationship of heterogeneous catalysts in asymmetric catalysis. Although several strategies including the use of chiral ligands and high‐performance liquid chromatography have been routinely employed to gain nanoclusters with inherent chirality, another simple methodology of spontaneous resolution remains largely unexplored. In this work, we report the isolation of homochiral Ag/Cu nanoclusters stabilized by alkynyl ligands from spontaneous self‐resolution, which represents a pioneering example in the realm of alkynyl‐protected metal nanoclusters. The cluster, with the formula of [Ag12 Cu7 (dppe)3 (RC≡C)14 ] 3+, has been prepared in one‐pot, with the high yield of 71%. Structural anatomy reveals that the metal architecture, metal‐ligand interface and ligand arrangement of the cluster all display chirality. The cluster features superatomic free electrons, implying its potential application in specific fields. This work not only offers strategic guidance for the simple synthesis of alkynyl‐protected metal nanoclusters with inherent chirality in an all‐achiral environment, but also displays the hierarchical chirality of cluster moieties at molecular level. Abstract : Homochiral Ag/Cu nanoclusters stabilized by alkynyl ligands have been prepared in high yield. In the absence of any chiral inducer, the chiral nanoclusters have been isolated in the crystalline form from spontaneous self‐resolution. The metal framework, metal‐ligand interface and surface ligands all exhibit clockwise arrangement, endowing it a model system to investigate chiral nanostructures at the molecular level.